Elemental Analysis on Marine Sediments Related to Depositional Environment of Bangka Strait - Pungky Sampurno; Rina Zuraida; Nazar Nurdin; Luli Gustiantini; Noor Cahyo Dwi Aryanto (BULLETIN OF THE MARINE GEOLOGY, 2017)
Study of elemental composition in sediment has been proven useful in interpreting the depositional environmental changes. Multi Sensor Core Logger (MSCL) is a non-destructive analysis that measures several parameters in sediment core including magnetic susceptibility and elemental composition. Magnetic susceptibility and elemental analysis were measured in four selected marine sediment cores from western part of Bangka Strait (MBB-67. MBB-119, MBB-120 and MBB-173) by using magnetic susceptibility and X-ray Fluorescence (XRF) sensors attached to the MSCL. The data was collected within 2 cm interval. Scatter plots of Y/Zr and Zr/Ti show singular trend demonstrated by sediments from MBB-173 and two groups that composed of MBB-67 (Group 1) and MBB-119 + MBB-120 (Group 2). MBB-67 that is located adjacent to Klabat Granite shows upward changes in mineralogy, slight increase of grain size and negligible change in Y concentration. Cores MBB-119 and MBB-120 are inferred to be deposited during regression that resulted in the accummulation of Y-bearing zircon in MBB-119 before the mineral could reach MBB-120. Core MBB-173 is interpreted to be the product of plagioclase weathering that is submerged by rising sea level. This core contains a horizon of rich Y-bearing zircon at 60 cm.Keywords: Multi Sensor Core Logger, X-Ray Fluorescence, magnetic susceptibility, depositional environment, Bangka Island Studi tentang komposisi unsur kimia dalam sedimen telah terbukti bermanfaat dalam interpretasi perubahan lingkungan pengendapan. Multi Sensor Core Logger (MSCL) adalah sebuah analisis yang non-destructive, untuk mengukur beberapa parameter dalam bor sedimen termasuk suseptibilitas magnetik dan kandungan unsur. Suseptibilitas magnetik dan kandungan unsur diukur dari 4 bor sedimen laut yang terpilih di bagian barat Selat Bangka (MBB-67. MBB-119, MBB-120 and MBB-173) dengan menggunakan sensor suseptibilitas magnetik (MS) dan X-ray Fluorescence (XRF) yang terpasang pada MSCL. Pengukuran dilaksanakan dengan interval 2 cm. Plot Y/Zr dan Zr/Ti menunjukkan satu trend yang diperlihatkan oleh sedimen bor MBB-173 dan dua grup yang terdiri atas MBB-67 (Grup 1) dan MBB-119 + MBB-120 (Grup 2). Bor MBB-173 ditafsirkan sebagai hasil pelapukan plagioklas yang kemudian terendam air laut. Bor ini memperlihatkan horizon yang kaya akan zirkon pembawa yttrium pada kedalaman 60 cm.Kata kunci : Multi Sensor Core Logger, X-Ray Fluorescence, suseptibilitas magnetik, lingkungan pengendapan, Pulau Bangka